CROSSLINK TELOPEPTIDA C-TERMINAL (CTx) SEBAGAI PETANDA AKTIVITAS SEL OSTEOKLAS PADA OSTEOPOROSIS PASCA MENOPAUSE DEFISIENSI ESTROGEN - Kawiyana, I Ketut Siki (journal of internal medicine; Vol. 10, No. 2 Mei 2009)
Osteoporosis occurs due to the increase of active osteoclastic bone resorption activity. This condition favors for bone mass decreased. The examination of Crosslink Telopeptida C-Terminal (CTx)serum concentration is a good indicator to determine osteoclastic bone resorption activity. The finding of that biochemical substance in serum indicates that there is increase of osteoclast cell activity. The aim of the study was to prove that in estrogen deficient post-menopausal women, the CTxwas higher in the osteoporosis compared than the non-osteoporosis. The study was an analytic-observational study in case-control design, which was done at Sanglah General Hospital, Denpasar. The sample size was 41 case subjects (osteoporosis) and 41 control subjects (non-osteoporosis) using paired case-control sample size formula. The t-paired test result were: CTx serum concentration was higher significantly in case compared than control (0.60 ± 0.22ng/mL vs 0.46 ± 0.16ng/mL; p = 0.004). Therefore from the study we may conclude that: (1) CTx was higher in the osteoporosis compared than the non-osteoporosis in estrogen deficient post-menopausal women. (2) Osteoclastic bone resoprtion activity was higher in the osteoporosis compared than the non-osteoporosis in estrogen deficient post-menopausal women
Keywords: Post-menopausal osteoporosis, estrogen, osteoclast activity, CTx